The given \(\displaystyle{3}{x}-{1}+{\frac{{{2}}}{{{7}}}}{\left({7}{x}-{2}\right)}=-{\frac{{{11}}}{{{7}}}}\).

The given phrase is an equation because it has an equal sign.

\(\displaystyle{3}{x}-{1}+{\frac{{{2}}}{{{7}}}}{\left({7}{x}-{2}\right)}=-{\frac{{{11}}}{{{7}}}}\)

\(\displaystyle{\frac{{{7}{\left({3}{x}-{1}\right)}+{2}{\left({7}{x}-{2}\right)}}}{{{7}}}}=-{\frac{{{11}}}{{{7}}}}\)

7(3x−1)+2(7x−2)=−11

21x−7+14x−4=−11

Step 2

Now, separate the variables on left side and constant of right side

21x+14x=−11+7+4

35x=−11+11

35x=0

x=0

Therefore, the value of x=0.